Pengawasan Market Conduct Terkait Transparansi Kredit Perbankan dalam Rangka Pelindungan Konsumen - meidia venny (Jurnal Hukum Lex Generalis, 2025)
This research analyzes OJK's market conduct supervision on banking credit transparency in consumer protection framework. Using empirical juridical methods, the study shows supervision regulations are comprehensively regulated in OJK Law, P2SK Law, OJK Regulation No. 22/2023, and OJK Circular Letter. Supervision implementation uses dual approach: direct supervision (thematic inspections, special examinations, field observations) and indirect supervision (IDR/EDR monitoring, advertising monitoring, self-assessment reports, risk analysis). Data shows banking sector has highest complaints (13,644 out of 35,939 total), indicating need for strengthening credit product transparency to optimally protect consumers.